Diversity of volatile patterns in sixteen Fragaria vesca L. accessions in comparison to cultivars of Fragaria ×ananassa ... - Ulrich, Detlef; Olbricht, Klaus (Journal of Applied Botany and Food Quality, 2013)
Fragaria vesca is the most distributed wild species in the genus Fragaria. Due to this biogeography a high diversity is to expect. During two harvest seasons sixteen accessions from different locations from the most eastern habitat at Lake Baikal in Siberia, from Middle and Southern Europe and Northern Europe with Scandinavia and Iceland were investigated as well as two of the three described North American subspecies and three F. vesca cultivars. Five very distinct European F. ×ananassa cultivars were chosen to serve as a comparison. Beside brix value and acid contents the aroma patterns including 67 volatile compounds were quantified by stir bar sorptive extraction followed by gas chromatography with mass spectrometric detection. The diversity of important volatiles of Fragaria vesca and F. ×ananassa is discussed regarding biogeography, domestication, breeding and the so-called funnel effect. ...